Differential modulation of thermal preference after sensitization by optogenetic or pharmacological activation of heat-sensitive nociceptors. (March 2021) - Li, Jerry; Zain, Maham; Bonin, Robert P
Common approaches to studying mechanisms of chronic pain and sensory changes in pre-clinical animal models involve measurement of acute, reflexive withdrawal responses evoked by noxious stimuli. These methods typically do not capture more subtle changes in sensory processing nor report on the consequent behavioral changes. In addition, data collection and analysis protocols are often labour-intensive and require direct investigator interactions, potentially introducing bias. In this study, we develop and characterize a low-cost, easily assembled behavioral assay that yields self-reported temperature preference from mice that is responsive to peripheral sensitization. This system uses a partially automated and freely available analysis pipeline to streamline the data collection process and enable objective analysis. We found that after intraplantar administration of the TrpV1 agonist, capsaicin, mice preferred to stay in cooler temperatures than saline injected mice. We further observed that gabapentin, a non-opioid analgesic commonly prescribed to treat chronic pain, reversed this aversion to higher temperatures. In contrast, optogenetic activation of the central terminals of TrpV1 + primary afferents via in vivo spinal light delivery did not induce a similar change in thermal preference, indicating a possible role for peripheral nociceptor activity in the modulation of temperature preference. We conclude that this easily produced and robust sensory assay provides an alternative approach to investigate the contribution of central and peripheral mechanisms of sensory processing that does not rely on reflexive responses evoked by noxious stimuli.